EFFECT OF SODIUM NITRITE, SODIUM SILICATE, HEXAMINE INHIBITORS AND THEIR BINARY MIXTURES ON INCREASING PITTING CORROSION RESISTANCE OF AISI 304 STAINLESS STEEL - XIUZHEN RAMITAN (NIM : 12508011), ALEXANDRA
AISI 304 stainless steel is an alloy that susceptible to localized corrosion in the environment containing Cl- ions. The presence of defects on the surface of AISI 304 stainless steel has siginificantly lowered its resistance to localized corrosion and the stainless steel will be more susceptible to pitting corrosion. One of the method that can be applied to decrease the localized corrosion susceptibility of AISI 304 stainless steel is to utilized proper inhibitors or various mixtures of inhibitors. The objective of this research is to study the influences of sodium nitrite, sodium silicate, and hexamine inhibitors addition, as well as the use of combination of these inhibitors (NaNO2 + Na2SiO3, NaNO2 + hexamine, Na2SiO3 + hexamine) with total concentration of 30 mmol/litre on the corrosion resistance of AISI 304 stainless steel in 3,56 gram/litre NaCl solution in room temperature. Polarization resistance and cyclic potentiodynamic technique have been used to study the effect of mixed inhibitors to pitting potential, corrosion rate, inhibition efficiency, and their synergistic effect. Polarization resistance measurement result indicates that the corrosion rate of AISI 304 stainless steel is 2,20x10-8 A/cm2 corrosion rate, while the pitting potential increased by cyclic polarization is 374,6 mV vs Ag/AgCl in the same test solution. Addition of inhibitors and mixed inhibitors has rised the pitting potential. The highest pitting potential obtained in this study (1184 mV vs Ag/AgCl) is in the test solution containing 15 mmol NaNO2 and 15 mmol Na2SiO3. Most of the experimental results do not exhibit synergistic effect of mixed inhibitors utilized in these tests. However, the presence of mixed inhibitors has increased the pitting potential of AISI 304 stainless steel. Thus, they increase the localized corrosion resistance.